2022
DOI: 10.1109/tap.2022.3191218
|View full text |Cite
|
Sign up to set email alerts
|

Channel Measurements and Modeling for Low Terahertz Communications in an Aircraft Cabin

Abstract: The low terahertz band (0.1 THz -1 THz) offers very high data rates for novel mobile applications and constitutes a promising candidate to meet the requirements in aviation, enabling future wireless in-flight entertainment systems. An extensive knowledge of the propagation effects in the radio channel in complex scenarios is a prerequisite to successfully design a communication system. This paper presents a measurement campaign in a real aircraft investigating the radio channel at 300 GHz for different deploym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…In the past years, various CBCS systems have become available [25], [26], [27], [28] allowing either dynamic measurements or reducing the measurement time in static environments significantly. CBCS have been widely used for measurements in various environments such as outdoor environments [27], office environments [26], industrial environments [29], data centers [30], trains [31], automotive [32], and aircrafts [33]. Recently, CBCS have also been used for channel characterisation with regard to the determination of key performance indicator (KPI) for physical layer security such as secrecy capacity [34], [35].…”
Section: Johannes M Eckhardt Tobias Doeker Thomas Kürner Naveed a Abb...mentioning
confidence: 99%
See 3 more Smart Citations
“…In the past years, various CBCS systems have become available [25], [26], [27], [28] allowing either dynamic measurements or reducing the measurement time in static environments significantly. CBCS have been widely used for measurements in various environments such as outdoor environments [27], office environments [26], industrial environments [29], data centers [30], trains [31], automotive [32], and aircrafts [33]. Recently, CBCS have also been used for channel characterisation with regard to the determination of key performance indicator (KPI) for physical layer security such as secrecy capacity [34], [35].…”
Section: Johannes M Eckhardt Tobias Doeker Thomas Kürner Naveed a Abb...mentioning
confidence: 99%
“…Measurements reported both in indoor [36], [23], [33], [29], and outdoor [40], [41] environments have shown that THz communications works also in non-line-of-sight (NLoS) situations by exploiting single or even multiple reflection or scattering processes, yielding a reduction of the received power level of compared to line-of-sight (LoS) as low as a few dB. Generally speaking, the pathloss coefficients for NLoS are in a similar range as those at cm-wave frequencies; however, shadowing is more severe, raising the probability of outage.…”
Section: A Common Insightsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measuring also relative values, the channel sounder has to be calibrated with respect to the amplitude and to the delay of the CIR with a back-to-back (B2B) calibration. By measuring the amplitude and the delay of known waveguides, a correction term can be calculated following the procedures described in [22] and [23], respectively. However, due to IQ-imbalances, the measurements are affected by an inaccuracy of up to ±2 dB but the calibration of the imbalances is an ongoing topic [24].…”
Section: A Measurement Equipmentmentioning
confidence: 99%